Deferred Prosecution Agreement dalam Pemidanaan Tindak Pidana Korupsi - Antari, Putu Eva Ditayani; Satriatama Adnyana, I Kadek Budiadinata (Universitas Muhammadiyah Bima, 2023)
Corruption is a persistent problem in Indonesia. The impact of corruption is very widespread which results in poverty and inhibits infrastructure development. Law enforcement for perpetrators of corruption in Indonesia still uses minimum and maximum imprisonment and in the form of fines. This resulted in the difficulty of recovering state financial losses due to corruption. So a new paradigm for criminalizing corruption is needed through the concept of the Deferred Prosecution Agreement (DPA). The aims of this study are 1) to find out the legal ratio of DPA application as an enforcement of corruption. 2) to find out the implementation of DPA in corruption crimes in Indonesia. Furthermore, this research method is a normative legal research method. This research method is used to examine studies in the form of books, journals, and regulations related to the author's research. The results of this study indicate that the correct basic concept used in criminal prosecution of corruption in Indonesia is the DPA concept from the UK, where the implementation is through negotiations between the prosecutor and the suspect and then the results of the negotiations are asked for the judge's opinion. Furthermore, after being approved by the judge, it will continue with the implementation of the contents of the DPA. So the concept of DPA is very appropriate to restore losses due to corruption.